2022
DOI: 10.1111/pce.14464
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall ester modifications and volatile emission signatures of plant response to abiotic stress

Abstract: Growth suppression and defence signalling are simultaneous strategies that plants invoke to respond to abiotic stress. Here, we show that the drought stress response of poplar trees (Populus trichocarpa) is initiated by a suppression in cell wall derived methanol (MeOH) emissions and activation of acetic acid (AA) fermentation defences. Temperature sensitive emissions dominated by MeOH (AA/MeOH <30%) were observed from physiologically active leaves, branches, detached stems, leaf cell wall isolations and whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 64 publications
1
14
1
Order By: Relevance
“…The high activity of fermentation metabolism in leaves under aerobic conditions (Fall, 2003) was proposed to explain large emission bursts of acetaldehyde lasting several minutes following light–dark transitions after a period of photosynthesis (Karl et al ., 2002). Subsequent studies found large emission bursts of not only acetaldehyde following light/dark transitions, but also ethanol, acetic acid, acetone, and methyl acetate (Jardine et al ., 2012, 2022a,b; Dewhirst et al ., 2021) with the magnitude of these bursts greatly increasing under hypoxia (Jardine et al ., 2012). While the biochemical origin of acetone biosynthesis in plants remains uncertain, one possibility is the decarboxylation of acetoacetate in a similar mechanism as in bacteria (Fall, 2003).…”
Section: Light–dark Transitions As Evidence For Fermentation Metaboli...mentioning
confidence: 99%
See 2 more Smart Citations
“…The high activity of fermentation metabolism in leaves under aerobic conditions (Fall, 2003) was proposed to explain large emission bursts of acetaldehyde lasting several minutes following light–dark transitions after a period of photosynthesis (Karl et al ., 2002). Subsequent studies found large emission bursts of not only acetaldehyde following light/dark transitions, but also ethanol, acetic acid, acetone, and methyl acetate (Jardine et al ., 2012, 2022a,b; Dewhirst et al ., 2021) with the magnitude of these bursts greatly increasing under hypoxia (Jardine et al ., 2012). While the biochemical origin of acetone biosynthesis in plants remains uncertain, one possibility is the decarboxylation of acetoacetate in a similar mechanism as in bacteria (Fall, 2003).…”
Section: Light–dark Transitions As Evidence For Fermentation Metaboli...mentioning
confidence: 99%
“…Using online mass spectrometry, temperature‐dependent emissions of acetaldehyde, ethanol, acetic acid, and methyl acetate were quantified in real‐time from individual leaves and branches during drought response in poplar trees (Dewhirst et al ., 2021; Jardine et al ., 2022a,b). Acetic acid emission has also been evaluated at the ecosystem scale using continuous vertical profiles of acetic acid ambient concentrations within and above a tropical forest canopy in South America (Jardine et al ., 2011) and in North America using the technique of eddy covariance where acetic acid emission fluxes are calculated every 30 min from the covariance between above canopy vertical wind speed and ambient acetic acid concentrations (Kim et al ., 2010; Park et al ., 2013).…”
Section: Remote Chemical Sensing Of Acetate Fermentation In Terrestri...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the non-specific sensors used were also able to detect volatiles emitted by the leaf but not to the resolution of specific molecules as used in other studies e.g. (Jardine et al, 2022; Jud et al, 2018). They were detected from V. vinifera leaves during the light-dark transition but not dark-light as observed in other studies (Jud et al, 2016) though for barley light-dark transitions appear to show a small peak in methanol emission (Jud et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively the sensitivity to methanol may be dependent on the transition phase or state of the stomata, that is, stomata may be less sensitive to methanol during the opening phase when methanol is normally released. Other alternatives exist to be further explored including that methanol may be part of a feedback system or that stomatal responses may depend on a combination of methanol with other VOCs, for example, acetic acid (Jardine et al, 2022).…”
Section: Methanol-induced Stomatal Closurementioning
confidence: 99%